Topical azithromycin for the prevention of Lyme borreliosis: a randomised, placebo-controlled, phase 3 efficacy trial. Issue 3 (March 2017) - Schwameis, Michael; Kündig, Thomas; Huber, Gustave; von Bidder, Luzi; Meinel, Lorenz; Weisser, Roland; Aberer, Elisabeth; Härter, Georg; Weinke, Thomas; Jelinek, Tomas; Fätkenheuer, Gerd; Wollina, Uwe; et al.
Summary: Background: Lyme borreliosis develops in 1–5% of individuals bitten by ticks, but with a diagnostic gap affecting up to 30% of patients, a broadly applicable pharmacological prevention strategy is needed. Topical azithromycin effectively eradicated Borrelia burgdorferi sensu lato from the skin in preclinical studies. We assessed its efficacy in human beings. Methods: In this randomised, double-blind, placebo-controlled, multicentre trial done in 28 study sites in Germany and Austria, adults were equally assigned to receive topical 10% azithromycin or placebo twice daily for 3 consecutive days, within 72 h of a tick bite being confirmed. Randomisation numbers, which were stratified by study site, were accessed in study centres via an interactive voice-response system, by pharmacists not involved in the study. The primary outcome was the number of treatment failures, defined as erythema migrans, seroconversion, or both, in participants who were seronegative at baseline, had no further tick bites during the study, and had serology results available at 8 weeks (intention-to-treat [ITT] population). This study is registered with EudraCT, number 2011-000117-39. Findings: Between July 7, 2011, and Dec 3, 2012, 1371 participants were randomly assigned to treatment, of whom 995 were included in the ITT population. The trial was stopped early because an improvement in the primary endpoint in the group receiving azithromycin was not reached. At 8 weeks, 11 (2%) of 505 in the azithromycin group and 11 (2%) of 490 in the placebo group had treatment failure (odds ratio 0·97, 95% CI 0·42–2·26, p=0·47). Topical azithromycin was well tolerated. Similar numbers of patients had adverse events in the two groups (175 [26%] of 505 vs 177 [26%] of 490, p=0·87), and most adverse events were mild. Interpretation: Topical azithromycin was well tolerated and had a good safety profile. Inclusion of asymptomatic seroconversion into the primary efficacy analysis led to no prevention effect with topical azithromycin. Adequately powered studies assessing only erythema migrans should be considered. A subgroup analysis in this study suggested that topical azithromycin reduces erythema migrans after bites of infected ticks. Funding: Ixodes AG.